Association of serum estrogen and melatonin levels with bone mineral density of post-menopausal women- a case-control study - Sadadiwala, Mehul Hitesh; Sadadiwala, Ashna (International Journal of Research in Medical Sciences, 2023)
Background: A skeleton is a metabolically active organ that constantly undergoes remodelling throughout life. Various factors influence the process of bone formation and resorption. Menopause is a crucial stage in a woman’s life and a female’s body undergoes many significant changes during this stage. Hormone-related changes occur not only due to menopause but also due to aging; the two crucial hormones we emphasized in our study are- estrogen and melatonin; and their manifestation in the skeletal system of a postmenopausal population. Methods: Our study consisted of 48 post-menopausal females, 24 subjects in the case group, and 24 in the control groups, to study the differences in certain parameters existing between the two. Serum estrogen and melatonin were calculated using the ELISA test; bone mineral density (BMD) was evaluated using a portable ultrasound bone densitometer testing machine. Results: The factors (estrogen and melatonin) have a direct strong linear relation with BMD. Pearson correlation coefficient was found to be positive (r) 0.92, indicating a strong correlation. The ‘goodness of fit’ (r2) of multiple linear regression was found to be 0.8485 (roundabout 85%), indicating strong positive results. Conclusions: The results of our study exhibited strong interdependence of BMD on serum estrogen and melatonin. Osteopenic subjects who had a lower BMD were also found to have relatively lesser levels of serum estrogen and melatonin. Aligning with the results, similarly, the control group with normal BMD was found to have relatively higher serum levels of both hormones.